FENOMENA PREDATORY PRICING DALAM PERSAINGAN USAHA DI E COMMERCE (STUDI KASUS ANTARA PENETAPAN TARIF BAWAH ANTARA APLIKASI INDRIVE DAN GOJEK) - Alem Savier Savier; Teddy Prima Anggriawan; Aldira Mara Ditta Caesar Purwanto (Peneliti.net, 2023)
During the Covid-19 pandemic, people took advantage of financial digitization for transactions so that there was an increase in e-commerce buying and selling transactions in Indonesia. This increase in e-commerce buying and selling transactions also occurred due to the practice of discount parties or massive discounts applied by e-commerce services. This massive discount could be an indication of a form of predatory pricing practice.